Potential Ecological Risk and Human Health Risk Assessment of Heavy Metal Pollution in Industrial Affected Soils by Coal Mining and Metallurgy in Ostrava, Czech Republic - Doležalová Weissmannová, Helena; Mihočová, Silvie; Chovanec, Petr; Pavlovský, Jiří (International journal of environmental research and public health, 2019)
The heavy metal pollution of soils has become serious environmental problem, mainly in localities with high industrialization and rapid growth. The purpose of this detailed research was to determine the actual status of heavy metal pollution of soils and an assessment of heavy metal pollution in a highly industrialized city, Ostrava, with a history of long-term impacts from the metallurgy industry and mining. The ecological risks to the area was subsequently also assessed. The heavy metals Cd, Hg, Cu, Mn, Pb, V, Zn, Cr and Fe were determined in top-soils (0-20 cm) using atomic absorption spectrometry (F AAS, GF AAS) from three areas with different anthropogenic loads. The obtained data expressed as mean metal concentrations were very varied among the sampled soils and values of all analyzed metal concentrations were higher than its background levels. To identify the ecological risk and assessment of soil pollution, various pollution indices were calculated, such as single pollution indices (Igeo, CF, EF, PI) and total complex indices (IPI, PLI, PINemerow, Cdeg, mCdeg, Er and PERI). The identification of pollution sources was assessed using Pearson's correlation analysis and multivariate methods (HCA, PCA/FA). The obtained results confirmed three major groups of metals (Fe-Cr, Pb-Cu and Mn-V). A human health risk was identified in the case of Pb, Cd and Cr, and the HI value of V for children also exceeded 1.
Keywords: monitorování životního prostředí; Metals, Heavy; látky znečišťující půdu; Cities; Metallurgy; Industrial Development; Česká republika; Risk Assessment; Environmental Monitoring; Adult; Czech Republic; dítě; těžké kovy; Child; těžba uhlí; znečištění životního prostředí; Soil Pollutants; Environmental Pollution; hodnocení rizik; Humans; Soil; Coal Mining; hutnictví; rozvoj průmyslu; velkoměsta; dospělí; spektrofotometrie atomová; půda; lidé; Spectrophotometry, Atomic